Molecular Evaluation of Soil Respiration in Crude Oil Pollution - Ebulue, Maximus M. (ASEAN Journal of Science and Engineering, 2023)
Oxygen diffusion into the soil ecosystem is imperative for the sustainability of life in the soil. This study evaluated selected microbial exudates as indices of soil respiration in a crude oil polluted soil ecosystem ex-situ using biochemical and physicochemical tools to determine the following parameters; total petroleum hydrocarbon (TPH), dehydrogenases, catalase, ATP, and pH. The result of the study at 1.5 – 3.5% contamination across days-zero to -28 following crude oil impact presented an augmented increase in TPH from 0.02 ± 0.00 to 0.10 ± 0.00 with an increase in the activity of soil dehydrogenases from 4.90 ± 0.01 to 8.80 ± 0.04 katal which was significant (p0.05). Conversely, the activity of soil catalase suffered inhibition from 0.20 ± 0.00 to 0.11 ± 0.00 katal. ATP synthesis decreased from control to 0.24 ± 0.00mg/100g on week one and increased to 0.60 ± 0.10mg/100mg significantly (p0.05) on week four with contamination as the pH was reduced from 5.8 ± 0.00 to 4.1 ± 0.00 significantly, thus creating hypoxia and a reducing environment, a demonstration of soil respiration.